(untitled) (ENTHYMEMA, 2020)
This essay investigates myth in Cesare Pavese’s narrative works from a Ricœurian perspective. It focuses on passages where the first-person narrator, at the tragic climax of the scene, introduces a sense of guilt. The importance of guilt to Pavese’s thought has often been given a biographical rationale, but this essay reexamines it in the light of a specific theory of myth. The steps in this reexamination are 1) tackling the problem of de-mythization, which is central to Pavese’s theoretical writings; 2) highlighting the link between guilt and a conception of time, including in narratological terms; and 3) showing how guilt does not arise from the author’s life but from his reflection on time, on the problem of evil, and on the finitude of human life.